Effect of core strength training on the badminton player`s performance: A systematic review & meta-analysis - Ma, S.; Soh, K. G.; Japar, S. B.; Liu, C.; Luo, S.; Mai, Y.; Wang, X.; Zhai, M. (PLOS ONE, 2024)
Background Core strength training (CST) has been shown to improve performance in several sports disciplines. CST is recognized as one of the crucial elements that enhance athletic performance, particularly impacting badminton skills. Despite its popularity as a strength training method among badminton players, there is a lack of comprehensive studies examining the effectiveness of CST on the performance of these athletes.